Gender-sensitive nutrition training in Embu County in Kenya - Ouya, Fredrick; Muriithi, Catherine; Lutomia, Cosmas Kweyu; Ketema, Dessalegn Molla; Waswa, Boaz; Nchanji, Eileen; Kagete, Murimi; Amboga, Seth; Magoti, Rahab; Nyokabi, Miriam; Nyaguthii, Mary; Wainaina, Miriam; et al. (2023)
The Gender Equality Initiative (HER+) Work Package 2 (WP 2) - EMPOWER targets to co-identify and model diverse scenarios for bundling climate-smart technologies to empower women, men and youths to be partners and drivers of climate change solutions. HER+ WP2 aims to integrate social innovations in existing Ukama Ustawi initiative (UU) sites or what we are calling learning labs to contribute to climate change resilience and women’s empowerment. The gender-sensitive nutrition training is one of the social and technical innovations that HER+ is integrating in existing UU sites in Nakuru, Makueni, and Embu Counties. HER+ in collaboration with UU and Kenya Agricultural Livestock Research Organization (KALRO) organized a three-day gender sensitive nutrition training in Embu in November 2023 following similar trainings in Nakuru and Makueni learning labs. The training aimed at contributing to equitable nutritional outcomes for women, men, youth, and children through awareness creation, nutritional education, towards reducing gender-based nutritional disparities.